Bartlett correction to the likelihood ratio test for MCAR with two‐step monotone sample. (28th April 2017) - Shutoh, Nobumichi; Nishiyama, Takahiro; Hyodo, Masashi
Abstract : Assuming that two‐step monotone missing data is drawn from a multivariate normal population, this paper derives the Bartlett‐type correction to the likelihood ratio test for missing completely at random (MCAR), which plays an important role in the statistical analysis of incomplete datasets. The advantages of our approach are confirmed in Monte Carlo simulations. Our correction drastically improved the accuracy of the type I error in Little's (1988, Journal of the American Statistical Association, 83, 1198–1202) test for MCAR and performed well even on moderate sample sizes.